ANALISIS PENGARUH KEMAMPUAN, UPAYA DAN DUKUNGAN PIHAK EKSTENAL TERHADAP KINERJA PEMILIK USAHA PADA UKM UNGGULAN MITRA BINAAN PT. SEMEN PADANG - Putri Andam Sari; Erni Masdupi (Program Studi Magister Manajemen, 2015)
The aim of this research were To know how is the ability, effort and eksternal support of owner of Small-Medium scale enterprenuer in PT. Semen Padang. The Research methods used Decriptive exploratives. And the competence Variable was described as three indicators which were ability, effort and eksternal support. To answer the research problems and test of hypothesis the researcher was used the statistics analysis with software SPSS, especially used the correlation analysis, regression, F-test dan t-test. Sample respondent used in this research was 155 respondens come from Small-Medium Scale Entrepreneur which clustered by PT. Semen Padang, and it was choosed by purposive sampling based on some criterias. The result of this research were as follows: (1) The competence of human resourch Small-Medium Scale enterprenuer was in fare categories, it is recommended to increase to be more competence enhance increasing their business performance globally. Furthermore, the hypothesis was accepted because regarding the result of F-test and t-test show that the ability,(2) effort and (3)Eksternal support was Significantly affected to the their business performance partially and simultaniusly its mean that the increasing in human resourch competence will be increase the business performance, eventhough eksternal support variable was most dominanly affected to the owner performance. Keywords: ability, effort,eksternal support, performance.